ENHANCING PROJECT MANAGEMENT EFFICIENCY IN THE DEVELOPMENT OF PUBLIC SERVICE COMPLAINT APPLICATIONS - Indah Dwijayanthi Nirmala; Ade Tamin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates how project management optimization can improve the development of an information-technology-based public complaint application. Grounded in the PMBOK framework and employing a Waterfall development approach, the research assesses how project planning, execution, monitoring, and closure contribute to efficiency, cost control, and product quality. Results reveal that structured project management strengthens stakeholder coordination, mitigates risks, and facilitates timely, budget-compliant delivery. The study recommends enhanced monitoring practices and capacity-building for project teams to sustain long-term benefits.